Prokaryotic and Eukaryotic Fecal Microbiota in Irritable Bowel Syndrome Patients and Healthy Individuals Colonized With Blastocystis - Nourrisson, Céline; Scanzi, Julien; Brunet, Julie; Delbac, Frédéric; Dapoigny, Michel; Poirier, Philippe (Frontiers in Microbiology, 2021)
Blastocystis is the most frequently isolated protozoan from human stool. Its role in human health is still debated, and a high prevalence was reported in irritable bowel syndrome (IBS) subjects suggesting a potential link with microbiota. In the present study we aimed to investigate prokaryotic and eukaryotic microbiota in both IBS-C (constipated) and healthy individuals. We recruited 35 IBS-C patients and 23 healthy subjects, from which 12 and 11 carried Blastocystis, respectively. We performed 16S- and 18S-rRNA high-throughput sequencing on feces. Whereas we did not observe differences between infected and non-infected controls, several phyla were significantly modified in IBS-C patients according to the presence of Blastocystis. Tenericutes phylum and Ruminococcaceae family were especially increased in Blastocystis carriers. Furthermore, colonization with Blastocystis was associated with discrete changes in the microbial eukaryome, particularly among the Fungi taxa. Depending on the group of patients considered, the mycobiota changes do not go in the same direction and seem more deleterious in the IBS-C group. These results encourage further in vivo and in vitro investigations concerning the role of Blastocystis in the gut environment.